Utilizing the Multiradionuclide Resolving Power of SPECT and Dual Radiolabeled Single Molecules to Assess Treatment Response of Tumors - Xu, Baogang (Mol Imaging Biol, 2015)
PURPOSE: Single photon emission computed tomography (SPECT) radionuclide pairs having distinct decay rates and different energy maxima enable simultaneous detection of dual gamma signals and real-time assessment of dynamic functional and molecular processes in vivo. Here, we report image acquisition and quantification protocols for a single molecule labeled with two different radionuclides for functional SPECT imaging. PROCEDURES: LS370 and LS734 were prepared using modular solid phase peptide synthesis. Each agent has a caspase-3 cleavable reporting motif, flanked by a tyrosine residue and a chelator at the opposite end of molecule. Cell uptake and efflux were assessed in human MDA-MB-231 breast cancer cells. Biodistribution studies were conducted in tumor naive and orthotopic 4T1 metastatic breast cancer tumor mice. NanoSPECT dual-imaging validation and attenuation correction parameters were developed using phantom vials containing varying radionuclide concentrations. Proof-of-principle SPECT imaging was performed in MMTV-PyMT transgenic mice. RESULTS: LS370 and LS734 were singly or dually radiolabeled with (125)I and (111)In or (99m)Tc. Cell assays demonstrated 11-fold higher percent uptake (P<0.001) of [(125)I]LS734 (3.6±0.5) compared to [(125)I]LS370 (0.3±0.3) at 2 h. Following chemotherapy, cellular retention of [(125)I]LS734 was 3-fold higher (P<0.05) than untreated cells. Pharmacokinetics at 1 h postinjection demonstrated longer blood retention (%ID/g) for [(125)I]LS734 (3.2±0.9) compared to [(125)I]LS370 (1.6±0.1). In mice bearing bilateral orthotopic 4T1 tumors, the uptake (%ID/g) was 2.4±0.3 for [(125)I]LS734 and 1.2±0.03 for [(125)I]LS370. The iodinated tyrosine peptide residue label was stable under in vitro conditions for up to 24 h; rapid systemic deiodination (high thyroid uptake) was observed in vivo. Phantom studies using standards demonstrated deconvolution of radionuclide signals based on different gamma ray energies. In MMTV-PyMT mice imaged with dual-labeled [(111)In]–[(125)I]LS734, the gamma signals were separable and quantifiable. CONCLUSIONS: Image processing protocols were developed for quantitative signal separation resulting from a caspase-3 responsive dual-radiolabeled SPECT probe. Crosstalk unmixing was obtained for multiradionuclide NanoSPECT imaging. In vitro and in vivo data demonstrated structure–activity relationships for developing functional agents for ratiometric SPECT imaging.